Influence of montmorillonite as secondary filler on the properties of carbon nanotube/high density polyethylene nanocomposites [electronic resource - Mohammed Ehtesham Ali Mohsin, 1985- author; Agus Arsad; Zurina Mohamad, supervisor (2014)
Thesis (Sarjana Kejuruteraan (Polimer)) - Universiti Teknologi Malaysia, 2014